1987
DOI: 10.1111/j.1398-9995.1987.tb00394.x
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary evaluation of the effect of N‐acetyl‐aspartyl‐glutamate on pollen nasal challenge as measured by rhinomanometry and symptomatology

Abstract: The preventive effect of a nasally administered single dose of the dipeptide N-acetyl-aspartyl-glutamate (NAAGA) on pollen-induced early nasal reaction as measured by rhinomanometry and symptomatology was investigated in a double-blind cross-over placebo controlled study in 18 patients with nasal sensitization to grass pollen. Mean nasal airways resistance at 20, 40, and 60 min post challenge was, respectively, 33%, 37% (P = 0.03) and 27% less after NAAGA than after placebo administration in the same patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In addition, Ghaem (1987) observed that a single dose of ZY15106 reduced the allergen-induced nasal obstruction as measured by anterior nasal rhinomanometry. These clinical findings may be explained, at least in part, by our results showing that 1-week local treatment with ZY15106 attenuates antigen-induced histamine and iLTC4 release in the nasal airways of allergic rhinitics.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, Ghaem (1987) observed that a single dose of ZY15106 reduced the allergen-induced nasal obstruction as measured by anterior nasal rhinomanometry. These clinical findings may be explained, at least in part, by our results showing that 1-week local treatment with ZY15106 attenuates antigen-induced histamine and iLTC4 release in the nasal airways of allergic rhinitics.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, ZY15106 was shown to inhibit mast cell degranulation induced by immunological and nonimmunological stimuli (Secchi et al 1987). In vivo, ZY15106 was proven to be able to reduce allergenevoked nasal symptoms (Ghaem et al 1987).…”
mentioning
confidence: 99%
“…An obvious example is the ability of sodium cromoglycate to inhibit the activation of human lung mast cells, but not skin mast cells (Clegg et al, 1985;Church, 1986). Thus, although NAAGA inhibits mast cell activation in the guinea-pig and partially inhibits the early nasal response to allergen challenge in human (Ghaem, 1987), it is not surprising to find that it is unable to protect the human lung mast cells against allergen challenge. Another possibility for its ineffectiveness could be due to an insufficient dose of aerosol administered, although a 3% solution of NAAGA was previously shown to be effective in stabilising guinea-pig mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NAAGA also inhibits activation of complement by both the classical and alternative pathways (unpublished data). This dipeptide, when administered as a nasal spray, has been shown to reduce allergen-induced nasal obstruction in patients with allergic rhinitis (Ghaem, 1987 None of them took any medication for at least 3 months prior to the study, or any time during the study. The study was approved by the Southampton University and Hospitals Ethics Sub-committee and written informed consent was obtained from each subject.…”
Section: Introduction Methodsmentioning
confidence: 99%
See 1 more Smart Citation